2021
DOI: 10.1089/neu.2020.7332
|View full text |Cite
|
Sign up to set email alerts
|

Blood Biomarkers for Detection of Brain Injury in COVID-19 Patients

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus attacks multiple organs of coronavirus disease 2019 (COVID-19) patients, including the brain. There are worldwide descriptions of neurological deficits in COVID-19 patients. Central nervous system (CNS) symptoms can be present early in the course of the disease. As many as 55% of hospitalized COVID-19 patients have been reported to have neurological disturbances three months after infection by SARS-CoV-2. The mutability of the SARS-COV-2 vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 338 publications
(299 reference statements)
1
92
0
Order By: Relevance
“…Further, Gigli et al suggested that some patients may have a specific genetic predisposition to postinfectious inflammatory syndromes and associated intrathecal cytokine responses after COVID-19 [ 98 ]. Of course, it is imperative to recognize that elevated CSF and serum biomarkers is not clearly indicative of neuroinvasion as this can result from other mechanisms such as hypoxic injury [ 267 , 268 ]. Additional research into treatment implications and the diagnostic and prognostic value of CSF biomarkers in patients with COVID-19 who have neurological symptoms is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Gigli et al suggested that some patients may have a specific genetic predisposition to postinfectious inflammatory syndromes and associated intrathecal cytokine responses after COVID-19 [ 98 ]. Of course, it is imperative to recognize that elevated CSF and serum biomarkers is not clearly indicative of neuroinvasion as this can result from other mechanisms such as hypoxic injury [ 267 , 268 ]. Additional research into treatment implications and the diagnostic and prognostic value of CSF biomarkers in patients with COVID-19 who have neurological symptoms is needed.…”
Section: Discussionmentioning
confidence: 99%
“…GFAP and UCH-L1 blood serum markers may also be useful for detecting the long lasting neurological damage found in some COVID-19 patients. 8 The findings of this study demonstrate the utility of using the two serum biomarkers GFAP and UCH-L1 for classification of diverse TBIs. This study is limited to small sample sizes for each type of pathology and necessitates investigation of larger sample sizes to overcome potential sampling bias.…”
Section: Discussionmentioning
confidence: 59%
“…The highest levels of GFAP were found in individuals diagnosed with skull fractures combined with ICH. 4 Additional research suggests that serum GFAP concentrations are an ideal biomarker to differentiate between various nontraumatic brain injuries such as ICH and acute ischemic stroke (AIS) with higher GFAP elevations presenting in cases where damage was more extensive 3,[5][6][7][8] Research on serum biomarkers has also shown that UCH-L1, an enzyme responsible for degradation in nerve cells, may also offer useful information in the classification and severity of brain injuries and has been associated with poor outcomes in individuals with both traumatic and nontraumatic brain injuries. 9 UCH-L1 is hypothesized to play a role in axon and neuronal repair by removing abnormal proteins that are present after injury.…”
Section: Introductionmentioning
confidence: 99%
“…PLR < 25%). Finally, high levels of serum biomarkers for brain injury, such as neuron specific enolase (NSE) and protein S-100β, have reported in COVID-19 patients ( DeKosky et al, 2020 ); their daily measurement could be discussed then at the medical round by the nursing team in patients with suspected brain injury if not prescribed by the attending doctors.…”
Section: How Nurses Can Adequately Use Neuromonitoring At the Bedsidementioning
confidence: 99%